Brønsted acid-promoted azide–olefin [3 + 2] cycloadditions for the preparation of contiguous aminopolyols: The importance of disiloxane ring size to a diastereoselective, bidirectional approach to zwittermicin A - Muchalski, Hubert; Hong, Ki Bum; Johnston, Jeffrey N. (Beilstein Journal of Organic Chemistry, 2010)
We report the first study of substrate-controlled diastereoselection in a double [3 + 2] dipolar cycloaddition of benzyl azide with α,β-unsaturated imides. Using a strong Brønsted acid (triflic acid) to activate the electron deficient imide π-bond, high diastereoselection was observed provided that a 1,1,3,3-tetraisopropoxydisiloxanylidene group (TIPDS) is used to restrict the conformation of the central 1,3-anti diol. This development provides a basis for a stereocontrolled approach to the aminopolyol core of (−)-zwittermicin A using a bidirectional synthesis strategy.
Keywords: azide; bidirectional synthesis; cycloaddition; dialkoxydisiloxane; TIPDS; triazoline; triflic acid; zwittermicin A